Online Performance Assessment Based on Science Process Skills and Collaboration Skills in Islamic Religious Higher Education - Latifah, Sri; Suryani, Yani; Sharov, Sergii (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2024)
4C skills (critical thinking, creativity, collaboration, communication) are essential in modern education. The existing assessment instruments are not fully integrated with technology. This research develops technology-based instruments to assess 4C skills.This study aims to determine experts' opinions on the feasibility and practicality of an online performance assessment instrument based on science process skills and collaboration skills. The research used the Research and Development method with the ADDIE development model. The subjects of the study were students from UIN Raden Intan Lampung, UIN Walisongo, and IAIN Cirebon with 60 students. The data collecting techniques used were questionnaires for expert validation on the content and language of the questions. The researcher also distributed questionnaires to the students. The findings of this study are 1) the final product meets the high feasibility criteria with a percentage of 88% for the content aspect and 86% for the language aspect, 2) the practicality of the product meets the excellent criteria, and 3) the response of the teachers indicates that the product is highly feasible. As a physics learning product in laboratory activities, the online performance assessment instrument with science process skills and collaboration skills is suitable and practical to use. It is recommended for other researchers to utilize other online platforms and instruments to measure other skills